Urban stormwater management tools (McGraw - Hill, 2004)
Managing stormwater flow is a particular challenge in urban environments. "Urban Stormwater Management Tools" details the design of basins and detection systems, covers subsurface and wetland issues, and presents a complete methodology for regulating sewer overflow. It includes methods for: hydrologically and hydraulically analyzing storm water systems; designing storm water inlets, storm sewers, detention systems and infiltration basins; learning about design methods ranging from the rational method to advanced simulation and optimization methods for sewer systems; integrating operations and management considerations into designs; and, performing risk/reliability analysis of stormwater systems.